2005
DOI: 10.1211/0022357055579
|View full text |Cite
|
Sign up to set email alerts
|

Lectin of Pisum arvense seeds induces in-vivo and in-vitro neutrophil migration

Abstract: PAL is a glucose/mannose-specific lectin isolated from Pisum arvense seeds. Previously, we demonstrated the capacity of other leguminous lectins to induce oedema formation and neutrophil stimulation. To investigate the potential pro-inflammatory activity of PAL, we have studied its ability to induce neutrophil migration into peritoneal cavities of rats and neutrophil chemotaxis in-vitro. The role of resident cells and sugar residues on PAL activity was analysed. PAL or saline (control) were administered intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
2
6
0
2
Order By: Relevance
“…Plant lectins, particularly monocot mannose-binding lectins, have shown pro-inflammatory effects. Vatairea macrocarpa lectin (VML), Pisum arvense lectin (PAL), Helianthus tuberosus lectin (HTL) and Dioclea rostrata lectin (DRL) induced acute inflammation through neutrophils migration in vivo, and injecting culture supernatants of DRA-stimulated macrophages in vivo significantly induced the release of TNF-α, IL-1β and NO in the mouse peritoneal fluid (5,6,(12)(13)(14)27). In our previous study, Arisaema erubescens lectin, which was derived from a plant in the Arisaema family, induced rat paw edema and in vivo neutrophil migration, possibly by releasing inflammatory mediators from macrophages (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant lectins, particularly monocot mannose-binding lectins, have shown pro-inflammatory effects. Vatairea macrocarpa lectin (VML), Pisum arvense lectin (PAL), Helianthus tuberosus lectin (HTL) and Dioclea rostrata lectin (DRL) induced acute inflammation through neutrophils migration in vivo, and injecting culture supernatants of DRA-stimulated macrophages in vivo significantly induced the release of TNF-α, IL-1β and NO in the mouse peritoneal fluid (5,6,(12)(13)(14)27). In our previous study, Arisaema erubescens lectin, which was derived from a plant in the Arisaema family, induced rat paw edema and in vivo neutrophil migration, possibly by releasing inflammatory mediators from macrophages (19).…”
Section: Discussionmentioning
confidence: 99%
“…Certain plant lectins are highly toxic in clinical and animal experiments, accompanied by neutrophil migration at inflammatory sites. Neutrophil migration into inflamed tissues is an important hallmark of acute inflammation, and resident macrophages have a critical role in triggering immune response and in inducing neutrophil infiltration at the early stage of damage (8)(9)(10)(11)(12)(13)(14). Inflammatory response is a complex phenomenon that involves vascular and cellular events.…”
Section: Introductionmentioning
confidence: 99%
“…Thioglycolate treatment raised the macrophage population 2.3 times causing elevation of neutrophil migration induced by CvL in 77%, but it did not modify the responsiveness to fMLP, a known direct chemoattractant. This novel finding showed that also a marine invertebrate lectin can modulate the neutrophil recruitment by indirect mechanisms like other exogenous lectins from plant origin, specially those purified from E. velutina (Moraes et al, 1996), Glycine max (Benjamin et al, 1997), T. esculenta (Freire et al, 2003), Vatairea macrocarpa (Alencar et al, 2003), Lonchocarpus sericeus (Alencar et al, 2005a), and Pisum arvense (Alencar et al, 2005b) seeds.…”
Section: Discussionmentioning
confidence: 93%
“…Lectins are ubiquitous (glyco)proteins of plant or animal origin possessing an ability to specifically bind carbohydrate moieties including cells (Dodd et al, 1968). Some lectins from plant origin, can mimic endogenous mammalian lectins and trigger in vivo and in vitro migration of specific leukocytes migration in various inflammation models (Alencar et al, 2005a;Alencar et al, 2005b;Coelho et al, 2006;Napimoga et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A capacidade das lectinas de se ligar aos açúcares é atribuível a uma porção limitada da molécula, correspondendo tipicamente a um domínio globular de reconhecimento de carboidrato (CRD) (ABREU et al, 2006 BARUFFI et al, 2001, RABINOVICH et al, 2002, CARVALHO et al, 2002. Lectinas de diversas fontes da natureza (animais e vegetais) foram estudadas para seu aspecto funcional na inflamação, na qual essas proteínas podem exercer atividades pró-inflamatórias (BENTO et al, 1993;ALENCAR et al, 2003ALENCAR et al, , 2005RUBSTEIN et al, 2004;TOLEDO et al, 2008) ou anti-inflamatórias (RABINOVICH et al, 1999;MOTA et al, 2006;NAPIMOGA et al, 2007) , 1984, , KOMORI et al,1999 Bitis (NIKAI et al, 1995), Bothrops (GARTNER et al, 1980, LOMONTE et al,1990, CARVALHO et al, 2002, GUIMARÃES-GOMES et al, 2004, OZEKI et al, 1994, HAVT et al, 2005, PANUNTO et al, 2006, Bungarus (ZHA et al,2001), Crotalus (GARTNER & OGILVIE, 1984), Dendroaspis (OLGILVIE et al, 1986), Lachesis 1986, OLGILVIE et al, 1986 e Trimeresurus (NIKAI et al, 2000).…”
Section: 4-lectinasunclassified